2002
DOI: 10.1074/jbc.m206382200
|View full text |Cite
|
Sign up to set email alerts
|

Functiona l Analysis of Eubacterial Diterpene Cyclases Responsible for Biosynthesis of a Diterpene Antibiotic, Terpentecin

Abstract: Eubacterial diterpene cyclase genes had previously been cloned from a diterpenoid antibiotic terpentecin producer (Dairi, T., Hamano, Y., Kuzuyama, T., Itoh, N., Furihata, K., and Seto, H. (2001) J. Bacteriol. 183, 6085-6094). Their products, open reading frame 11 (ORF11) and ORF12, were essential for the conversion of geranylgeranyl diphosphate (GGDP) into terpentetriene (TTE) that had the same basic skeleton as terpentecin. In this study, functional analyses of these two enzymes were performed by using purif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 46 publications
6
73
0
Order By: Relevance
“…We named this new product as terpentedienol diphosphate (TDP, 2), based on structural similarities to TTE (3) and the presence of two double bonds and a diphosphate. We also confirmed that TDP (2) was converted into TTE (3) by Cyc2, showing that TDP (2) is the real intermediate converted from GGDP (1) by Cyc1 [76].…”
Section: Function Of Cyc1 and Cyc2supporting
confidence: 75%
See 1 more Smart Citation
“…We named this new product as terpentedienol diphosphate (TDP, 2), based on structural similarities to TTE (3) and the presence of two double bonds and a diphosphate. We also confirmed that TDP (2) was converted into TTE (3) by Cyc2, showing that TDP (2) is the real intermediate converted from GGDP (1) by Cyc1 [76].…”
Section: Function Of Cyc1 and Cyc2supporting
confidence: 75%
“…Under this reaction condition, the formation of TTE (3) was confirmed [76]. On the other hand, TTE (3) was not formed by the enzyme reaction in which Cyc2 was used first, followed by inactivation and the addition of Cyc1.…”
Section: Function Of Cyc1 and Cyc2mentioning
confidence: 74%
“…GGDP was purchased from Sigma-Aldrich and further purified by column chromatography to remove such impurities as Mg 2þ . 25) All other chemicals were of analytical grade. The plasmid, pGEX-4T3 {N-terminal glutathione S-transferase-(GST) fused, GE Healthcare}, was used for expressing the recombinant enzymes.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the three pGGxC constructs reported here will be useful for characterization of novel class I labdane-related diterpene synthases. Finally, we expect that a similar approach will provide access to labdane-related diterpenes and diterpenoid natural products derived from other class II intermediates such as clerodadienyl diphosphate (i.e., by incorporating class II diterpene cyclases that produce such compounds 15 into pGG), which will further broaden the reach of the modular approach to labdane-related diterpene biosynthesis demonstrated here. (5) a E. coli containing the indicated plasmid(s) produce the indicated labdane-related diterpene, as identified by GC-MS based comparison to authentic standards, with production levels ranging from 5 to 100 µg diterpene/L mixed phase culture (see Supporting Information).…”
mentioning
confidence: 99%